Sistem Numeralia dalam Bahasa Namblong - Yulius Pagappong (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Numeral is a word for counting the number of people, animals, things, and consepts. Basically, there are two kinds of numeral as Indonesian, they are cardinal and ordinal. Cardinal refers to the answer of question "how many and how much". Ordinal explains the answers of question "which". Most of Papuan knows three numeral systems; Indonesian system, hand and foot system, and parts of body system.